Reinterpretasi Cerita Rakyat menjadi Cerita Anak untuk Meningkatkan Kemampuan Menulis Kreatif Mahasiswa - Afrodita, Meli; Hiasa, Fina; Lazfihma; Ismawati, Dwi; Sari, Dwi Lyna; Yanti, Nafri; Chanafiah, Yayah (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study aims to develop literary learning to improve students' creative writing skills in internalizing local cultural values through the reinterpretation of folk tales into children's stories. This study uses a Classroom Action Research approach with two cycles. Each cycle involves planning, implementation, observation, and reflection. The results of the study indicate that the application of a learning model based on the reinterpretation of folk tales into children's stories is effective in improving children's literary writing skills rooted in local cultural values. This is evidenced by the improvement in students' work from the pre-cycle, cycle I, to cycle II, with average scores of 68.3, 76.4, and 85.2, respectively. A total of 28 children's stories were produced, each containing local cultural values in a relevant and easily understandable form for children. Students not only improved technically in terms of writing structure, language, and characters but also demonstrated the ability to creatively and contextually incorporate local cultural values. This learning process encouraged them to reflect on their regional cultural heritage and channel it through educational and engaging children's literature